1974
DOI: 10.1002/jhet.5570110639
|View full text |Cite
|
Sign up to set email alerts
|

Anilinopyrylium salts. Their synthesis and conversion to other heterocyclic systems

Abstract: Two methods for the preparation of anilinopyrylium salts are described. The conversion of these salts to pyrans, pyridines, and nitrobenzenes is discussed. Azepines, benzimidazoles, and benxotriazoles are readily obtained from the o‐aminoanilinopyrylium salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Compounds 4 were found to exhibit at the NMR time scale E, Z-conformational equilibrium at the exocyclic C, N bond. Surprisingly, no experimental evidence for such equilibrium was provided by earlier reports on N-4,6-triphenylpyran 2-imine (4, R = R' = Ph) [2][3][4][5] or other pyran 2-imines 6,7 and benzoannelated analogs [8][9][10][11][12][13] . By contrast, the hindered rotation around C,N double bond in Naryl-2,6-dimethyl-4H-pyran-4-imines 5 and related iminium salts 6, 7 (Scheme 2) had been extensively investigated by 1 H, 13 C and 15 N NMR in the early eighties.…”
Section: Methodsmentioning
confidence: 99%
“…Compounds 4 were found to exhibit at the NMR time scale E, Z-conformational equilibrium at the exocyclic C, N bond. Surprisingly, no experimental evidence for such equilibrium was provided by earlier reports on N-4,6-triphenylpyran 2-imine (4, R = R' = Ph) [2][3][4][5] or other pyran 2-imines 6,7 and benzoannelated analogs [8][9][10][11][12][13] . By contrast, the hindered rotation around C,N double bond in Naryl-2,6-dimethyl-4H-pyran-4-imines 5 and related iminium salts 6, 7 (Scheme 2) had been extensively investigated by 1 H, 13 C and 15 N NMR in the early eighties.…”
Section: Methodsmentioning
confidence: 99%
“…synthetized as described in the literature,14,15 was added. The mixture was stirred at reflux temperature for 3 h, then cooled at room temperature and stirred for 20 h. The solvent was removed under reduced pressure and the resulting brownish, red oil used for the next step without purification.4.1.3.…”
mentioning
confidence: 99%
“…To explore whether similar anomeric effects are found in other heterocyclic rings with exocyclic substituents, we have calculated properties of the pyrone derivatives 17a-d. N,4,6-Triphenypyran-2-imines are known [23,24], and Uncuţa and coworkers, in a detailed NMR study, have shown that in equilibrium mixtures, e.g., 17b,c, the trans (Z) configuration prevails [25].…”
Section: Resultsmentioning
confidence: 99%